2021
DOI: 10.1096/fba.2021-00002
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and care for patients with chronic kidney disease: Challenges and lessons

Abstract: The COVID-19 pandemic has blurred the traditional distinction between communicable diseases (CD) and noncommunicable diseases (NCDs). The manifestations of COVID-19 range from an asymptomatic carrier state to fatal multiorgan failure. While initial reports did not report significant effects on the kidneys, it is now well established that kidney involvement (acute kidney injury, urinary abnormalities, tubular function defects) in COVID-19 is common and also associated with poorer outcomes. At the same time, car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“… 33 The COVID‐19 infection has been related to kidney dysfunction which then increases the risk of mortality. 37 The challenges that CKD patients faced during the pandemic include operating healthcare services, available healthcare workers, and access to important medications and diagnostics, especially for those who require dialysis or kidney transplant. 37 A study from India discussed the effect that the pandemic has done on dialysis patients, and it showed that approximately 30% of patients missed at least one session of dialysis and 3% required emergency dialysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 33 The COVID‐19 infection has been related to kidney dysfunction which then increases the risk of mortality. 37 The challenges that CKD patients faced during the pandemic include operating healthcare services, available healthcare workers, and access to important medications and diagnostics, especially for those who require dialysis or kidney transplant. 37 A study from India discussed the effect that the pandemic has done on dialysis patients, and it showed that approximately 30% of patients missed at least one session of dialysis and 3% required emergency dialysis.…”
Section: Resultsmentioning
confidence: 99%
“…It is the fourth most common chronic illness that causes serious COVID‐19 infection outcomes 33 . The COVID‐19 infection has been related to kidney dysfunction which then increases the risk of mortality 37 . The challenges that CKD patients faced during the pandemic include operating healthcare services, available healthcare workers, and access to important medications and diagnostics, especially for those who require dialysis or kidney transplant 37 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The case fatality rate in patients receiving chronic dialysis in the developed world has been documented to be significantly higher than that of the general population [6], approaching 30% in some series [7]. Comorbidities such as ischaemic heart disease, diabetes mellitus, and hypertension, as well as the advanced age of the dialysis population in these series are likely contributors to the excess mortality in these reports [1].…”
Section: Introductionmentioning
confidence: 73%
“…In-centre haemodialysis is associated with an increased risk of acquiring infection with the novel Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2) through healthcare-associated transmission of the virus [1]. Prolonged viral shedding in patients living with kidney failure (KF) may compound the risk of infection through patient-to-patient transmission [2,3].…”
Section: Introductionmentioning
confidence: 99%